2013
DOI: 10.1534/genetics.113.155978
|View full text |Cite
|
Sign up to set email alerts
|

Is the Fungus Magnaporthe Losing DNA Methylation?

Abstract: The long terminal repeat retrotransposon, Magnaporthe gypsy-like element (MAGGY), has been shown to be targeted for cytosine methylation in a subset of Magnaporthe oryzae field isolates. Analysis of the F 1 progeny from a genetic cross between methylation-proficient (Br48) and methylation-deficient (GFSI1-7-2) isolates revealed that methylation of the MAGGY element was governed by a single dominant gene. Positional cloning followed by gene disruption and complementation experiments revealed that the responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Although the DNA methylation status of a long terminal repeat retrotransposon (LTR), Magnaporthe gypsy‐like element (MAGGY), differs among various Magnaporthe grisea subgroups (fungal isolates derived from rice, common millets, foxtail millet and torpedo grass) (Nakayashiki et al ., ), its inactivation could not be attributed to DNA methylation in M. grisea (Nakayashiki et al ., ). Analyses of the F1 progeny derived through the cross of methylation‐proficient (Br‐48) and methylation‐deficient (GFSI1‐7‐2) isolates revealed the role of MoDMT1 (DNMT), an orthologue of N. crassa Dim‐2 , in the methylation of MAGGY elements (Ikeda et al ., ). However, phenotypic analyses of the MoDMT1 mutant revealed no significant role of MoDMT1 in the regulation of the development and pathogenicity of M. oryzae (Ikeda et al ., ).…”
Section: Mechanisms Of Epigenetic Modifications In M Oryzaementioning
confidence: 97%
See 3 more Smart Citations
“…Although the DNA methylation status of a long terminal repeat retrotransposon (LTR), Magnaporthe gypsy‐like element (MAGGY), differs among various Magnaporthe grisea subgroups (fungal isolates derived from rice, common millets, foxtail millet and torpedo grass) (Nakayashiki et al ., ), its inactivation could not be attributed to DNA methylation in M. grisea (Nakayashiki et al ., ). Analyses of the F1 progeny derived through the cross of methylation‐proficient (Br‐48) and methylation‐deficient (GFSI1‐7‐2) isolates revealed the role of MoDMT1 (DNMT), an orthologue of N. crassa Dim‐2 , in the methylation of MAGGY elements (Ikeda et al ., ). However, phenotypic analyses of the MoDMT1 mutant revealed no significant role of MoDMT1 in the regulation of the development and pathogenicity of M. oryzae (Ikeda et al ., ).…”
Section: Mechanisms Of Epigenetic Modifications In M Oryzaementioning
confidence: 97%
“…Analyses of the F1 progeny derived through the cross of methylation‐proficient (Br‐48) and methylation‐deficient (GFSI1‐7‐2) isolates revealed the role of MoDMT1 (DNMT), an orthologue of N. crassa Dim‐2 , in the methylation of MAGGY elements (Ikeda et al ., ). However, phenotypic analyses of the MoDMT1 mutant revealed no significant role of MoDMT1 in the regulation of the development and pathogenicity of M. oryzae (Ikeda et al ., ). Furthermore, a trend of a loss in DNA methylation was observed in 60 field isolates of M. oryzae .…”
Section: Mechanisms Of Epigenetic Modifications In M Oryzaementioning
confidence: 97%
See 2 more Smart Citations
“…Genomic evidence indicates that RIP occurs or at least has occurred in the life history of most fungi including several Aspergilli (e.g., Aspergillus nidulans, Aspergillus niger, Aspergillus fumigatus, and Aspergillus oryzae (Clutterbuck et al 2008)) and other biotechnologically relevant taxa such as Trichoderma and Penicillium (Kubicek et al 2011;Braumann et al 2008). In Magnaporthe oryzae and Magnaporthe grisea, Ikeda et al (2013) detected mutations in DNA methyltransferases (see below) in a high portion of wild-type isolates and concluded that DNA methylation is on the way to be lost from this fungus. It is possible that this is also the case with other fungi, which would explain the partially conflicting results.…”
Section: Dna Methylationmentioning
confidence: 99%